PROFITABILITY ANALYSIS OF LATE WET SEASON TOMATO (LWST) PRODUCTION AMONG SMALLHOLDER PRODUCERS IN KADUNA STATE, NIGERIA - Abdulkadir, M.B.; Suleiman, A.; Suleiman, M.S.; Wahab, M.J. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study analyzed the profitability of late wet season tomato (LWST) production in Kaduna State, Nigeria. A multi-stage sampling procedure was employed to select 296 tomato producers for this study. Primary data were collected using a well-structured questionnaire. Data collected were analysed using descriptive statistics, farm budgeting techniques, multiple regression. The finding revealed that the tomato producers were literate with mean age of 41years and were mostly married; majority of them had household sizes between 1 and 14 persons with a mean tomato production experience of 16years. The result also showed that an average total variable cost (TVC) of ₦352,784.4 per hectare was incurred while total revenue (TR) of ₦604,000 per hectare was realized with an operating ratio of 0.58 and a return per naira invested (ROI) of ₦0.71k. This implies that for every ₦1.00 invested, ₦0.71k was realized by the tomato producers. This revealed that late wet season tomato production was profitable in the study area. The result of factors influencing profitability revealed that years of experience, membership of association, farm size (ha) and extension visit were found to be significant at 1%, 5% and 10% levels of probability respectively. The study concludes that late wet season tomato producers operate on a small-scale with high productive potential. LWST was a lucrative enterprise with a number of parameters determining the enterprise profitability. The study recommended that Kaduna Agricultural Development Agency should increase the frequency and quality of extension visits, with a focus on disseminating best practices for late wet season tomato production.